Intra-Arterial Drug and Light Delivery for Photodynamic Therapy Using Visudyne®: Implication for Atherosclerotic Plaque Treatment - Jain, Manish; Zellweger, Matthieu; Frobert, Aurélien; Valentin, Jérémy; Bergh, Hubert van den; Wagnières, Georges; Cook, Stéphane; Giraud, Marie-Noelle (Frontiers in Physiology, 2016)
Photodynamic therapy (PDT), which is based on the activation of photosensitizers with light, can be used to reduce plaque burden. We hypothesized that intra-arterial photosensitizer administration and photo-activation will lead to high and rapid accumulation within the plaque with reduced systemic adverse effects. Thus this “intra-arterial” PDT would be expected to have less side effects and due to the short time involved would be compatible with percutaneous coronary interventions. Aim: We characterized the dose-dependent uptake and efficacy of intra-arterial PDT using Liposomal Verteporfin (Visudyne®), efficient for cancer-PDT but not tested before for PDT of atherosclerosis. Methods and Results: Visudyne® (100, 200 and 500 ng/ml) was perfused for 5-30 minutes in atherosclerotic aorta isolated from ApoE-/- mice. The fluorescence Intensity (FI) after 15 minutes of Visudyne® perfusion increased with doses of 100 (FI-5.5 ± 1.8), 200 (FI-31.9 ± 1.9) or 500 ng/ml (FI-42.9 ± 1.2). Visudyne® (500 ng/ml) uptake also increased with the administration time from 5 minutes (FI-9.8 ± 2.5) to 10 minutes (FI-23.3 ± 3.0) and 15 minutes (FI-42.9 ± 3.4) before reaching saturation at 30 minutes (FI-39.3 ± 2.4) contact. Intra-arterial PDT (Fluence: 100 and 200 J/cm2, irradiance-334 mW/cm2) applied immediately after Visudyne® perfusion (500 ng/ml for 15 minutes) using a cylindrical light diffuser coupled to a diode laser (690 nm), led to an increase of ROS (Dihydroethidium) (FI-6.9 ± 1.8, 25.3 ± 5.5, 43.4 ± 13.9) and apoptotic cells (TUNEL) (2.5 ± 1.6 %, 41.3 ± 15.3 %, 58.9 ± 6 %), mainly plaque macrophages (immunostaining) (0.3 ± 0.2 %, 37.6 ± 6.4 %, 45.3 ± 5.4 %) at light doses of 0, 100 or 200 J/cm2 respectively. Limited apoptosis was observed in the medial wall (0.5 ± 0.2 %, 8.5 ± 4.7 %, 15.3 ± 12.7 %). Finally, Visudyne®-PDT was found to be associated with reduced vessel functionality (Myogram). Conclusion: We demonstrated that sufficient accumulation of Visudyne® within plaque could be achieved in short-time and therefore validated the feasibility of local intravascular administration of photosensitizer. Intra-arterial Visudyne®-PDT preferentially affected plaque macrophages and may therefore alter the dynamic progression of plaque development.